Adult glioblastoma with Lynch syndrome-associated mismatch repair deficiency forms a distinct high-risk molecular subgroup - Georgescu, Maria-Magdalena (Free Neuropathology, 2024)
Glioblastoma is the most frequent and malignant primary brain tumor. Although the survival is generally dismal for glioblastoma patients, risk stratification and the identification of high-risk subgroups is important for prompt and aggressive management. The G1–G7 molecular subgroup classification based on the MAPK pathway activa-tion has offered for the first time a non-redundant, all-inclusive classification of adult glioblastoma. Five patients from the large, 218-patient, prospective cohort showed germline mutations in mismatch repair (MMR) genes (Lynch syndrome) and a significantly worse median survival of 3.25 months post-surgery than those from the G1/EGFR and G3/NF1 major subgroups, or from the rest of the cohort adjusted for age. These rare tumors were assigned to a new subgroup, G3/MMR, a G3/NF1 subgroup spin-off, as they generally show genomic alterations leading to RAS activation, such as NF1 and PTPN11 mutations. An integrated clinical, histologic and molecular analysis of the G3/MMR tumors showed distinct characteristics as compared to other glioblastomas, including those with iatrogenic high tumor mutation burden (TMB), warranting a separate subgroup. Prior history of cancer, midline location or multifocality, presence of multinucleated giant cells (MGCs), positive p53 and MMR immunohistochemistry, and specific molecular characteristics, including high TMB, MSH2/MSH6 alterations, biallelic T53 Arg mutations and co-occurring PIK3CA p.R88Q and PTEN alterations, alert to this high-risk G3/MMR subgroup. The MGCs and p53 immunohistochemistry analysis in G1–G7 subgroups showed that one in 7 tumors with these characteristics is a G3/MMR glioblastoma. The FDA-approved first-line therapy for many advanced solid tumors consists of nivolumab-ipilimumab immune checkpoint inhibitors. One G3/MMR patient received this regimen and survived much longer than the rest, setting a proof-of-principle example for the treatment of these very aggressive G3/MMR glioblastomas.